1993
DOI: 10.1136/jcp.46.7.672
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic leukaemia with trisomy 8 and double gammopathy.

Abstract: Prolonged eosinophilia of unknown cause has generally been described as the hypereosinophilic syndrome, and is characterised by peripheral blood and bone marrow infiltration and frequent multisystem disease. The nature of this disorder has been questioned, and the clinical features are quite variable, suggesting its heterogeneity and probable neoplastic aetiology.A patient with severe eosinophilia, karyotype abnormalities, serum gammopathy and massive organ disease is reported. The clinical course was aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It has been speculated that the erb B oncogene, localized to 7p12.3-p12.1, is amplified as a result of this translocation, but, its association with the pathogenesis of MDS is controversial [16, 17]. In our case, trisomy 8 was also involved, which has been observed not only in conjunction with MDS-Eo [2, 12, 13], but also with CEL [18, 19]or idiopathic hypereosinophilic syndrome [20, 21]. In MDS-Eo, trisomy 8 has been reported in 5 cases, including the present case [2, 11, 12, 22].…”
Section: Discussionmentioning
confidence: 69%
“…It has been speculated that the erb B oncogene, localized to 7p12.3-p12.1, is amplified as a result of this translocation, but, its association with the pathogenesis of MDS is controversial [16, 17]. In our case, trisomy 8 was also involved, which has been observed not only in conjunction with MDS-Eo [2, 12, 13], but also with CEL [18, 19]or idiopathic hypereosinophilic syndrome [20, 21]. In MDS-Eo, trisomy 8 has been reported in 5 cases, including the present case [2, 11, 12, 22].…”
Section: Discussionmentioning
confidence: 69%
“…Following the initial report, numerous case reports or small series of patients with eosinophilic leukaemia have been reported (Saito et al, 1985;Kueck et al, 1991;Weinfeld et al, 1977;Ribeiro et al, 1993), although until today no report has shown conclusively that the eosinophils are monoclonal (Fauci et al, 1982). Chromosome abnormalities have been reported in most cases of eosinophilic leukaemia including trisomies of chromosomes 8, 10 or 21 (Saito et al, 1985;Goldman et al, 1975;Kueck et al, 1991;Weinfeld et al, 1977;Ribeiro et al, 1993). Additional translocations such as the t(2;5) (p23;q35) have been reported (Sato et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Also in a case with refractory anaemia, markedly increased eosinophils were found, but the aberrant karyotype was not found in the eosinophils (Perez-Losada et al, 1994). In HES, several patients with different chromosome abnormalities have been decribed, which suggests a malignant monoclonal myeloproliferative disorder in these cases (Malbrain et al, 1996;Broustet et al, 1986;Mori et al, 1986;Fischkoff et al, 1988;Yoo et al, 1988;Needleman et al, 1990;Ribeiro et al, 1993;Sato et al, 1994). However, these cases lacked direct evidence that the eosinophils were part of the malignant clone.…”
mentioning
confidence: 99%
“…We believe, on the basis of our own experience and of reports from the literature (Liesveld & Abboud, 1991;Malbrain et al, 1994;Zabel & Schlaak, 1991) that in those selected patients CSA can have a role, because it acts to suppress the activation of T lymphocytes and to decrease the output of regulatory cytokines that stimulate eosinophil production from these lymphocytes (Liesveld & Abboud, 1991). Table III lists the chromosomal abnormalities that have been previously reported in association with HES or eosinophilic leukaemia (Baumgarten et al, 1989;Bitran et al, 1977;Broustet et al, 1986;Cabrol, 1979;Chan et al, 1994;Da Silva et al, 1988;Ellman et al, 1979;Fischkoff et al, 1988;Goffman et al, 1983;Goh et al, 1985;Goldman et al, 1975;Guitard et al, 1994;Huang et al, 1979;Humphrey et al, 1981;Kaneko et al, 1983;Keene et al, 1987;Lönnqvist et al, 1979;Maeda et al, 1985;Michel et al, 1991;Mitelman et al, 1975;Needleman et al, 1990;Parreira et al, 1986;Ribeiro et al, 1993;Stockdill et al, 1980;Tono-oka et al, 1984;Weinfeld et al, 1977;Wolz et al, 1993;Yoo et al, 1984). Trisomy 8 is a common finding in myeloid haematological malignancies and has been reported in association with eosinophilic leukaemia or HES in six cases (Bitran et al, 1977;Goh et al, 1985;…”
Section: Discussionmentioning
confidence: 99%